MEDIASI SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA PERCERAIAN DAN DAMPAKNYA TERHADAP KESEHATAN - Abdul Rahman Maulana Siregar (Jurnal Keluarga Sehat Sejahtera, 2025)
Mediation as an alternative way to resolve marital disputes is one way to create a more equitable resolution process. The process emphasizes communication and mutual agreement between the parties, thereby reducing the emotional tension that often arises in litigation. Through mediation, disputing couples are given space to express their opinions and find mutually beneficial solutions without having to go through a lengthy court process. From a health perspective, mediation has a positive impact because it can reduce stress, depression, and psychological distress commonly experienced by divorcing couples. Furthermore, mediation also contributes to the mental health stability of children affected by divorce, as the process is more peaceful and prioritizes family well-being. Thus, mediation serves not only as an alternative legal instrument but also as a means of psychological and social recovery for the disputing parties. This research confirms that the application of mediation in divorce disputes can be an effective and healthy solution, both from a legal perspective and for the health of individuals and families.